Identification of Five Key Genes Involved in Intrinsic Apoptotic Pathway From Yellow Catfish Pelteobagrus fulvidraco and Their Transcriptional Responses to High Fat Diet (HFD) - Li, Dan-Dan; Ling, Shi-Cheng; Wu, Kun; Luo, Zhi (Frontiers in Physiology, 2019)
The hypothesis of the present study is that apoptosis through an intrinsic mitochondrial pathway may mediate high fat diet (HFD)-induced changes in the metabolism of Pelteobagrus fulvidraco. To this end, we cloned the full-length cDNA sequences of Cycs, Apaf1, Casp9, Casp3a, and Casp3b involved in the mitochondria apoptotic pathway, and explored their mRNA tissue expressions and transcriptional responses to HFD. All of these members shared similar domains to their orthologous vertebrate genes. They were constitutively expressed in all analyzed tissues but varied from tissue to tissue. Compared to the control, HFD up-regulated the mRNA expression of partial genes among these five key genes (Cycs, Apaf1, Casp9, Casp3a, and Casp3b) in mesenteric fat, intestine, ovary and the kidney, indicating the induction of apoptosis in these tissues; in contrast, HFD down-regulated mRNA levels of partial genes among the five key genes (Cycs, Apaf1, Casp9, Casp3a, and Casp3b) in the heart, spleen and gill tissues, indicating the inhibition of apoptosis in these tissues. The present study will facilitate further exploration into the functions of these genes at the molecular level and disclose the critical involvement of these genes against nutrient changes, indicating that processes of apoptosis in various tissues may differentially be modified by HFD.